2000
DOI: 10.1016/s0014-5793(00)01356-9
|View full text |Cite
|
Sign up to set email alerts
|

Genotype dependent and cigarette specific effects on endothelial nitric oxide synthase gene expression and enzyme activity

Abstract: We explored the interactive effects of endothelial nitric oxide synthase (eNOS) genotypes and cigarette smoking on protein levels and enzyme activity in 33 postpartum placentas. Whilst the eNOS protein levels were lower in the rare allele (0.48 þ 0.11, n = 9 vs. 1.05 þ 0.10, n = 24, P 6 0.01), the eNOS enzyme activity was about 7-fold higher in the rare allele (4556.2 þ 255.4 vs. 621.8 þ 180.5 cpm/mg/min, P 6 0.01). Smokers had lower eNOS protein levels (1.07 þ 0.09 vs. 0.50 þ 0.19, P 6 0.05) in both alleles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
138
2
5

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(161 citation statements)
references
References 25 publications
9
138
2
5
Order By: Relevance
“…It was reported that smoking decreases activity of eNOS and may modify the relationship between polymorphisms and expression levels. 20,21 For that reason, we performed multiple binary regression analysis (Table 4). Although smoking was a more powerful risk factor than 27-bp repeat polymorphism in total FHON patients, 4a allele was the only variable with statistical significance after adjustment of the effect of smoking in idiopathic group (p c ¼ 0.026, OR 4.302, 95% CI 1.359-13.621).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that smoking decreases activity of eNOS and may modify the relationship between polymorphisms and expression levels. 20,21 For that reason, we performed multiple binary regression analysis (Table 4). Although smoking was a more powerful risk factor than 27-bp repeat polymorphism in total FHON patients, 4a allele was the only variable with statistical significance after adjustment of the effect of smoking in idiopathic group (p c ¼ 0.026, OR 4.302, 95% CI 1.359-13.621).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms of these two polymorphisms affecting eNOS activity are different. Glu298Asp polymorphism induces the structural change of the eNOS protein and reduces eNOS activity [10,11]. In contrast, a different study showed that in -786T-C mutation, replication protein A1 which is known as a DNA binding protein essential for DNA repair and replication, binds only to the mutant allele and reduces the promoter activity of the eNOS gene [12,28].…”
Section: Discussionmentioning
confidence: 97%
“…Two major polymorphisms have been found in the human eNOS gene: Glu298Asp (G894T) in exon 7 and -786T-C mutation in the 5′-flanking region. Glu298Asp causes a structural change of the eNOS Endothelial derived nitric oxide (NO), synthesized from L-arginine by the endothelium isoform of NO synthase (eNOS), mediates local vasodilation and plays protein and reduces eNOS activity [10,11]. In contrast, the -786T-C mutation reduces the promoter activity [12] and thus reduces eNOS protein expression and eNOS activity [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One recent example of the latter was noted in studies on the vascular endothelial nitric oxide (NO) synthase (eNOS) system. Changes in tissue NO levels occur in patients with chronic hypertension, atherosclerosis, and thrombotic disorders, and polymorphic forms of eNOS have been described [56], as have mutations in the promoter sequence for this gene [57]. One variant, the eNOS 4/4 allele, appears particularly sensitive to an environmental influence (cigarette smoke), and inducible changes in eNOS gene expression may be a useful model for the study of external influences on triggering SCD in high-risk genotypes.…”
mentioning
confidence: 99%